Bicameral conflict resolution in an asymmetrical Parliament: nine case studies from the House of Lords 1976-2012 - Williams, Fiona (2018)
The House of Lords has been rising in profile in academic, political, and popular narratives. Whilst existing research has developed our understanding of the House of Lords and its role in bringing about defeats of the Government and the genesis and paths of amendments made within both chambers, there has been little distinction made between how the Lords brings about a defeat, and the Lords bringing about a defeat that is later overturned. Equally, the role of the Lords in amending a bill as a reviewing chamber, and amending one as a second chamber in its own right have not been separated. Research into comparable international examples has shown that this period between an amendment being moved and a defeat being sustained or overturned can define the bicameral relationship, and it is this area of the House of Lords relationship with the wider British political system that this thesis examines. This thesis studies the extent to which the Lords attempts and succeeds with amendments to bills, looking at the changes in both as the procedure known as ping pong progresses. It also examines the behaviour changes, both through debate language and through tangible voting turnout as, ping pong progresses to build up a picture of behaviour within the chamber. This thesis bridges the gap between the procedural single case study model and the large scale defeats and amendment tracing study model to show that the House of Lords has become a chamber that is driven more than ever by historical and political realities, as well as the political needs of the policy in question. This research argues that the House of Lords maintains a delicate balance between two roles, that of a second chamber which is performing a function complimentary to and distinct from that of the first chamber in passing legislation and that of a chamber that is aware of its somewhat uncomfortable position as a non-democratic institution, filled with non-directly elected members. Ultimately in the House of Lords, for ping pong to begin there is a need for strong feeling on the policy in question. The House of Lords ability to achieve its aims is measured in three points, first in its desired amendments to legislation, second in its actions as ping pong divisions progress, and the debates leading to them take place and lastly in the final degree of conciliation it achieves. In all three points, the role of self restraint has a positive role in achieving an outcome that is closest to the Lords original aims, whilst still allowing the Government's legislative programme and aims to pass. It is this understanding that allows the Lords to have the greatest influence over legislation, and perform a significant role.